2018
DOI: 10.1038/s41567-018-0279-5
|View full text |Cite
|
Sign up to set email alerts
|

Active wetting of epithelial tissues

Abstract: Development, regeneration and cancer involve drastic transitions in tissue morphology. In analogy with the behavior of inert fluids, some of these transitions have been interpreted as wetting transitions. The validity and scope of this analogy are unclear, however, because the active cellular forces that drive tissue wetting have been neither measured nor theoretically accounted for. Here we show that the transition between two-dimensional epithelial monolayers and three-dimensional spheroidal aggregates can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
293
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(315 citation statements)
references
References 92 publications
20
293
2
Order By: Relevance
“…Due to the complexity of collective behaviors, much effort has gone towards reductionist assays that restrict degrees of freedom and ensemble size to simplify analysis and interpretation. One powerful approach is to confine a tissue within predefined boundaries using micropatterning to create adhesive and non-adhesive regions (6)(7)(8)(9)(10)(11). Such confinement mimics certain in vivo contexts such as constrained tumors as well as aspects of compartmentalization during morphogenesis (12).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity of collective behaviors, much effort has gone towards reductionist assays that restrict degrees of freedom and ensemble size to simplify analysis and interpretation. One powerful approach is to confine a tissue within predefined boundaries using micropatterning to create adhesive and non-adhesive regions (6)(7)(8)(9)(10)(11). Such confinement mimics certain in vivo contexts such as constrained tumors as well as aspects of compartmentalization during morphogenesis (12).…”
Section: Introductionmentioning
confidence: 99%
“…By studying cell behaviour of 3D spheroidal aggregates placed on a solid and adhesive substrate, it was observed that over time the 3D cluster starts to spread on the substrate forming a 2D layer with cells individually leaving the cluster, a hallmark of EMT (Douezan et al, 2011). The reverse transition, also called de-wetting, was found in epithelial 2D monolayers, where increasing the level of E-cadherin triggers a sudden morphological transition into 3D clusters (Pérez-González et al, 2019). The reverse transition, also called de-wetting, was found in epithelial 2D monolayers, where increasing the level of E-cadherin triggers a sudden morphological transition into 3D clusters (Pérez-González et al, 2019).…”
Section: Occurrence and Function Of Potential Phase Transitions In Dementioning
confidence: 99%
“…This process was further described by a wetting behaviour depending on the levels of E-cadherin, where highly cohesive aggregates are in a liquid state, while in weakly cohesive aggregates, cells escape and undergo a liquid-to-gas transition (Douezan et al, 2011) (Glossary). Theoretical modelling suggested that this de-wetting transition is triggered at a critical point of cell contractility regulated by the E-cadherin levels, and cellsubstrate adhesion energy regulated by substrate ligand density and monolayer size (Pérez-González et al, 2019). Theoretical modelling suggested that this de-wetting transition is triggered at a critical point of cell contractility regulated by the E-cadherin levels, and cellsubstrate adhesion energy regulated by substrate ligand density and monolayer size (Pérez-González et al, 2019).…”
Section: Occurrence and Function Of Potential Phase Transitions In Dementioning
confidence: 99%
See 1 more Smart Citation
“…By studying their deformation dynamics, the relative viscosity of spreading cell aggregates could be deduced (11). On adhesive substrates, it has been shown that shape fluctuations caused by active tractions may induce morphological instabilities that introduce a colony size dependency to the wetting transition (13). On soft and/or weakly adhesive substrates, cells are unable to generate significant substrate traction forces.…”
Section: Introductionmentioning
confidence: 99%